Portuguese Youth Religiosity in Comparative Perspective - Coutinho, José Pereira (Religions, 2023)
Portugal has been a good example of sociocultural changes during the last decades which have influenced the levels of religiosity, namely among young people. In this context, this article studies Portuguese youth religiosity in a comparative perspective. First, it compares Portuguese youth religiosity with the other Portuguese age groups’ religiosity. Second, it compares Portuguese youth religiosity over time. A supplementary analysis compares Portugal with Catholic Europe in both aspects. Portuguese youth are less religious than the other age groups, mainly the older group, and are becoming less religious over time. Comparing Portugal with Catholic Europe, differences in young people have decreased in the last two decades, reaching similar values in 2020. Quantitative analyses based on four religiosity dimensions (community, practice, belief, and norm), using the European Values Study, were applied. These data confirm secularization, including the theories of individualization and cohort replacement, in line with other studies.